Novos dados de ocorrência de oito espécies de Ophioninae (Hymenoptera: Ichneumonidae) no Brasil. - Onody, Helena Carolina; Dias, Angélica Maria Penteado (ENTOMOTROPICA, 2007)
Eight new records of Ophioninae (Hymenoptera: Ichneumonidae) species for Brazil are presented: Enicospilus hacha Gauld, 1988; Enicospilus lebophagus Gauld, 1988; Enicospilus maculipennis (Cameron, 1886); Enicospilus stevensi Gauld, 1988; Enicospilus ulfstrandi Gauld, 1988; Ophion calliope Gauld, 1988; Ophiogastrella lemairei Gauld, 1988 and Prethophion latus Townes, 1971. Distribution information in different Brazilian ecosystems is presented.